I survived : the attacks of September 11, 2001 - Ball, Georgia (I survived (Graphic novel series), 2021)
When Lucas's parents tell him he needs to quit football because it is too dangerous, he skips school to go and talk to his football hero and uncle, Benny. That day was September 11, 2001, and Lucas is trapped in the city when the planes hit the towers.